Catalytic enantioselective synthesis of chiral spirocyclic 1, 3-diketones via organo-cation catalysis. Issue 85 (11th October 2021) - Zhang, Xiao-Yan; Shao, Ya-Ping; Guo, Bao-Kuan; Zhang, Kun; Zhang, Fu-Min; Zhang, Xiao-Ming; Tu, Yong-Qiang
Abstract : Herein, an SPA-triazolium bromide catalyzed asymmetric transannular C -acylation of enol lactones is described, providing a novel approach to access chiral spirocyclic 1, 3-diketones. Abstract : An SPA-triazolium bromide-catalyzed transannular C -acylation of enol lactones is presented. This methodology provides convenient access to a range of enantioenriched spirocyclic 1, 3-diketones in moderate to high yields and enantioselectivities and features a broad substrate scope in terms of enol lactones. The catalytic capability of this triazolium salt catalyst is also demonstrated in this enantioselective transformation, which could inspire its further application.